2015
DOI: 10.19084/rca15024
|View full text |Cite
|
Sign up to set email alerts
|

Carências de boro no interior - norte e centro - de Portugal

Abstract: R E S U M OEm Portugal, a deficiência de boro tem sido observada em quase todo o território, particularmente no interior, causando prejuízos assinaláveis nas culturas. Foi reconhecida pela primeira vez na década de 50 do séc. XX, nas vinhas do Douro (designada de 'maromba'). Desde os anos 80 vêm sendo realizados estudos sistemáticos no interior norte/centro do país para identificação e correcção desta carência em fruteiras e espécies florestais/agroflorestais. Neste trabalho de revisão faz-se uma inventariação… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Studies conducted in northern Portugal showed that chestnut may display symptoms of B deficiency (Portela and Louzada, 2012;Portela et al, 2015b) and responds to the application of the nutrient as a fertilizer (Portela et al, 2011(Portela et al, , 2015a, as do other important crops in the region, such as olive (Arrobas et al, 2010;Rodrigues et al, 2011). In the north of Portugal, symptoms of Mg deficiency also seem to occur with some frequency, at least in some lithological formations (Portela et al, 2003(Portela et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in northern Portugal showed that chestnut may display symptoms of B deficiency (Portela and Louzada, 2012;Portela et al, 2015b) and responds to the application of the nutrient as a fertilizer (Portela et al, 2011(Portela et al, , 2015a, as do other important crops in the region, such as olive (Arrobas et al, 2010;Rodrigues et al, 2011). In the north of Portugal, symptoms of Mg deficiency also seem to occur with some frequency, at least in some lithological formations (Portela et al, 2003(Portela et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…), since this is the main source of B (Gonçalves et al, 2015). Such conditions predispose to nutrient deficiency in the plant, not possibly supplying crop requirements throughout the vegetative cycle (Portela et al, 2015).…”
Section: Introductionmentioning
confidence: 99%